Clinical Features and Long-Term Outcomes After Laparoscopic Surgery in Patients Co-existing With Endometriosis and Adenomyosis - Sun, Ting-Ting; Li, Xiao-Yan; Shi, Jing-Hua; Wu, Yu-Shi; Gu, Zhi-Yue; Leng, Jin-Hua (Frontiers in Medicine, 2021)
Objective: To investigate the difference of clinical features and outcomes between EM patients with and without AM after following up for at least 6 years after surgery. Methods: We retrospectively analyzed 358 EM patients who had a minimum of 6 years follow-up after laparoscopic cystectomy, which was performed by one single doctor at Peking Union Medical College Hospital from January 2009 to April 2013. All women were divided into AM group and non-AM group and analysis was performed in preoperative characteristics, surgical findings and postoperative outcomes during follow-up. Results: A total of 358 EM patients were recruited, of which 142 (39.7%) were in the AM group and the rest 216 (60.3%) in the non-AM group. Between the two group, the mean age was 34.6 vs 32.2 years (P＜0.001). The mean operating time in the AM and non-AM group was 73.2 vs 61.9 minutes (P< 0.001). According to the revised AFS classification, the mean score of the two group were 60.3 vs 45.5 (P< 0.001). At the end of the follow-up, though the AM group was with higher rate of disease relapse, yet no significant difference was found between the two groups in statistical comparison (34/142 [23.9%] vs 34/216 [15.7%], P= 0.053). With a minimum follow-up of 6 years after laparoscopic cystectomy, failed and successful pregnancy were seen in 107/142(75.4%) and 35/142 (24.6%) patients in the AM group vs 114/216(52.8%) and 102/216 (47.2%) patients in the non-AM group (P< 0.05). As for the successfully pregnant patients, live births, including spontaneous pregnancy and IVF-ET, were seen in 34/35 (97.1) vs 99/102 (97.1) patients between AM and non-AM groups, while others ended in spontaneous abortion. No significant associations were found between the two groups in infertility, leiomyoma presence, the size of ovarian endometrioma, type of deep infiltrating endometriosis (DIE) or type of recurrence (P> 0.05). Conclusion: Compared with non-AM group, EM patients with concurrent AM may have higher age, longer mean operating time and higher mean AFS score. In terms of fertility outcomes, patients in the AM group were with lower likelihood of pregnancy after surgery during the long-time follow-up.